EFEKTIVITAS KOMUNIKASI ORGANISASI PADA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KOTA TASIKMALAYA - icha restika; Rozeries Agri Saerity; Widi Maulida Latifah; Siti Syalwa Nurfitriyani; Desi Guniati Putri; Robby Agny El-Varessy Bachtiar (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2026)
Organizational communication plays an important role in supporting the effectiveness of task implementation in disaster management institutions because it is related to coordination, information delivery, and decision-making during emergency situations. This study aimed to determine the effectiveness of organizational communication at the Regional Disaster Management Agency of Tasikmalaya City in supporting organizational duties and functions. This study employed a qualitative approach using a descriptive method. Data were collected through interviews and documentation involving two informants selected using a purposive sampling technique. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that organizational communication at the Regional Disaster Management Agency of Tasikmalaya City had been implemented effectively through a structured communication system supported by various communication media in disaster management activities. The communication process was carried out through a clear flow, starting from receiving information, coordinating activities, to implementing actions in the field. Although several obstacles were identified, such as network disruptions, panic situations, and differences in work priorities among institutions, various efforts had been made to overcome these challenges. Therefore, effective organizational communication plays an important role in supporting coordination and disaster management implementation.